Zakat and Green Finance: Formulating a Green Zakat Model to Support Energy Transition and Climate Change Adaptation - Mohammad Musa; Muhammad Firdaus (Raudhatun Najah Publisher, 2026)
Ideally, zakat should function not only as an instrument for socio-economic empowerment but also as a driver of ecological transformation in responding to the climate crisis. In reality, however, the utilization of zakat to support energy transition and climate-change adaptation remains fragmented, lacks operational models, and is not yet integrated into the national green finance framework. This study aims to formulate a Green Zakat Model that systematically connects Islamic principles, environmental sustainability, and climate mitigation–adaptation strategies. The research employs an exploratory qualitative approach through policy analysis, extensive international literature review, and in-depth interviews with zakat institutions, Islamic economics experts, and green-energy stakeholders. Data were analyzed using thematic coding to identify patterns, opportunities, and barriers to integrating zakat within the green finance ecosystem. The findings show that zakat holds strategic potential to finance community-based energy resilience, low-carbon technologies, ecological rehabilitation, and adaptation programs for vulnerable groups. The proposed model presents a governance framework, maqashid-based green project criteria, and accountability mechanisms aligned with global green finance standards. These results highlight that zakat can serve as a catalyst for an inclusive and socially–ecologically just energy transition.